2020
DOI: 10.1097/pec.0000000000002208
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal Administered Epinephrine Is Effective in Return of Spontaneous Circulation Within a Pediatric Swine Hypovolemic Cardiac Arrest Model

Abstract: Objective: Early administration of epinephrine increases the incidence of return of spontaneous circulation (ROSC) and improves outcomes among pediatric cardiac arrest victims. Rapid endotracheal (ET) intubation can facilitate early administration of epinephrine to pediatric victims. To date, no studies have evaluated the use of ETepinephrine in a pediatric hypovolemic cardiac arrest model to determine the incidence of ROSC.Methods: This prospective, experimental study evaluated the pharmacokinetics and/or inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…To compare the efficacy of epinephrine between differing routes of administration, Yauger et al used a hypovolemic pediatric swine model to compare intravenous with endotracheal administration of epinephrine. This study found that by using the guideline-recommended doses of epinephrine for each route, endotracheal administration led to more frequent ROSC and in a shorter timeframe [15]. This study provides an endorsement of the endotracheal route of administration but should be interpreted in a clinical context as the pigs studied were intubated before the time of arrest.…”
Section: Description Of the State Of Knowledgementioning
confidence: 79%
“…To compare the efficacy of epinephrine between differing routes of administration, Yauger et al used a hypovolemic pediatric swine model to compare intravenous with endotracheal administration of epinephrine. This study found that by using the guideline-recommended doses of epinephrine for each route, endotracheal administration led to more frequent ROSC and in a shorter timeframe [15]. This study provides an endorsement of the endotracheal route of administration but should be interpreted in a clinical context as the pigs studied were intubated before the time of arrest.…”
Section: Description Of the State Of Knowledgementioning
confidence: 79%
“…The time course of ET administered epinephrine was similar in the hypovolemic and normovolemic models. However, the time to maximum plasma concentration of IV administered epinephrine was greater in the hypovolemic model (111 ± 14 seconds) than in the normovolemic model 17 The delay in peak epinephrine concentration after IV administration in the hypovolemic model when compared with the normovolemic model may reflect poor circulation at the peripheral site of administration, that is, auricular vein.…”
Section: Discussionmentioning
confidence: 89%
“…We previously examined the pharmacokinetics of ET and IV administered epinephrine in a hypovolemic pediatric cardiac arrest model 17 . In comparison to the normovolemic model, the time courses of plasma epinephrine after ET and IV administration were similar in the hypovolemic model 17 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations